2015
DOI: 10.18632/oncotarget.3969
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of a large panel of patient-derived hepatocellular carcinoma xenograft tumor models for preclinical development

Abstract: Lack of clinically relevant tumor models dramatically hampers development of effective therapies for hepatocellular carcinoma (HCC). Establishment of patient-derived xenograft (PDX) models that faithfully recapitulate the genetic and phenotypic features of HCC becomes important. In this study, we first established a cohort of 65 stable PDX models of HCC from corresponding Chinese patients. Then we showed that the histology and gene expression patterns of PDX models were highly consistent between xenografts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 45 publications
7
77
0
Order By: Relevance
“…Another major limitation consistently observed across the different approaches is the low efficacy of successful generation of patient‐derived models which questions if these models can cover a representative spectrum of human liver cancer. In our study, efficacy of generating PLC‐PDCLs reached 11%, a similar range as observed in other solid malignancies and with application of other approaches (usually ranging from 10 to 33%) . However, identification of factors contributing to successful establishment of PDCL and subsequent optimization of the culture conditions is urgently needed to establish large and representative repositories required for extensive studies in PLC.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another major limitation consistently observed across the different approaches is the low efficacy of successful generation of patient‐derived models which questions if these models can cover a representative spectrum of human liver cancer. In our study, efficacy of generating PLC‐PDCLs reached 11%, a similar range as observed in other solid malignancies and with application of other approaches (usually ranging from 10 to 33%) . However, identification of factors contributing to successful establishment of PDCL and subsequent optimization of the culture conditions is urgently needed to establish large and representative repositories required for extensive studies in PLC.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study extended the organoid culture system for PLC and derived organoids from HCC, CCA and mixed HCC/CCA and demonstrated that PLC organoids faithfully recapitulated the molecular profile of the original tumors . Further, only few studies exploited the potential of PDx as well as PDCL as a model for liver cancer . Regardless of the primary approach, all the available patient‐derived models have important common as well as specific limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the amplification of FGF3/FGF4 genes and FGF21 overexpression has recently been observed in an HCC patient (34,35). A subpopulation of HCC patients with FGFR1 overexpression was thought to be addicted to FGFR1 (36). FGFR2 and FGFR3 overexpression contributed to advanced HCC tumorigenesis (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of ASP5878 over FGFR4-selective inhibitors is the ability to provide therapeutic benefit to a subset of patients with HCC whose tumors are driven by FGFR1, 2, or 3. In addition to FGFR4, the overexpression of FGFR1, FGFR2, and FGFR3 contributes to advanced HCC tumorigenesis, metastasis, and poor prognosis (36)(37)(38). In particular, Paur and colleagues observed that FGFR3 and/or FGFR4 expression was elevated in 68% of HCC patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the available data on liver cancers were very limited . Another limitation of the published HCC PDX models is that all of these have been generated from surgically resected HCCs . Because surgical resections are predominantly performed in patients with early stage tumors (typically Barcelona Clinic Liver Cancer [BCLC] stages 0/A), PDXs derived from resected tumors are heavily biased against advanced‐stage HCCs.…”
mentioning
confidence: 99%